Higher Morbidity of Monogenic Inflammatory Bowel Disease Compared to the Adolescent Onset Inflammatory Bowel Disease - Kim, Kwang Yeon (Pediatr Gastroenterol Hepatol Nutr, 2018)
PURPOSE: Monogenic inflammatory bowel disease (IBD) patients do not respond to conventional therapy and are associated with a higher morbidity. We summarized the clinical characteristics of monogenic IBD patients and compared their clinical outcomes to that of non-monogenic IBD patients. METHODS: We performed a retrospective cohort study of all children <18 years old who were diagnosed with IBD between 2005 and 2016. A total of 230 children were enrolled. Monogenic IBD was defined as a presentation age less than 6 years old with confirmation of a genetic disorder. We subdivided the groups into monogenic IBD (n=18), non-monogenic very early-onset IBD (defined as patients with a presentation age <6 years old without a confirmed genetic disorder, n=12), non-monogenic IBD (defined as all patients under 18 years old excluding monogenic IBD, n=212), and severe IBD (defined as patients treated with an anti-tumor necrosis factor excluding monogenic IBD, n=92). We compared demographic data, initial pediatric Crohn disease activity index/pediatric ulcerative colitis activity index (PCDAI/PUCAI) score, frequency of hospitalizations, surgical experiences, and height and weight under 3rd percentile among the patients enrolled. RESULTS: The initial PCDAI/PUCAI score (p<0.05), incidence of surgery per year (p<0.05), and hospitalization per year (p<0.05) were higher in the monogenic IBD group than in the other IBD groups. Additionally, the proportion of children whose weight and height were less than the 3rd percentile (p<0.05 and p<0.05, respectively) was also higher in the monogenic IBD group. CONCLUSION: Monogenic IBD showed more severe clinical manifestations than the other groups.